Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/healthcare6040120
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Properties of The Delayed Childbearing Questionnaire (DCBQ-55)

Abstract: The comprehensive assessment of delayed childbearing needs a valid and reliable instrument. Therefore, the aim of the present study was to develop an instrument to evaluate factors influencing delayed childbearing among women and to assess its psychometric properties. The current methodological study was performed in two phases of (i) qualitative instrument development, and (ii) quantitative psychometric assessment of the developed instrument. Face and content validity of the instrument was assessed by eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…China is not alone in confronting a shrinking population. It has been reported that nearly half of the world's population now live in countries with fertility rates at or below replacement level, and nearly all countries will reach low fertility levels in the next two decades [3][4][5]. The long-term low fertility rate will lead to a high level of aging and population decline, which will bring multiple socio-economic challenges [26].…”
Section: Baby Robots and Parenting Promotionmentioning
confidence: 99%
See 1 more Smart Citation
“…China is not alone in confronting a shrinking population. It has been reported that nearly half of the world's population now live in countries with fertility rates at or below replacement level, and nearly all countries will reach low fertility levels in the next two decades [3][4][5]. The long-term low fertility rate will lead to a high level of aging and population decline, which will bring multiple socio-economic challenges [26].…”
Section: Baby Robots and Parenting Promotionmentioning
confidence: 99%
“…Declining populations are creating many social problems in countries where this phenomenon is occurring [3][4][5]. To address this issue, some scholars and practitioners have exerted efforts to understand the mechanism of fertility promotion globally [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%